Expanding the Phenotypic and Genetic Spectrum of Neuromuscular Diseases Caused by DYNC1H1 Mutations - Li, Jia-Tong; Dong, Si-Qi; Zhu, Dong-Qing; Yang, Wen-Bo; Qian, Ting; Liu, Xiao-Ni; Chen, Xiang-Jun (Frontiers in Neurology, 2022)
Objectives: Spinal muscular atrophy, lower extremity-predominant 1 (SMALED1), and Charcot-Marie-Tooth type 2O (CMT2O) are two kinds of hereditary neuromuscular diseases caused by DYNC1H1 mutations. In this study, we reported two patients with SMALED1 caused by DYNC1H1 mutations. The genotype-phenotype correlations were further analyzed by systematically reviewing previous relevant publications. Materials & Methods: Two SMALED1 patients and their parents' clinical data were collected, and detailed clinical examinations were performed. WES was then applied, which was confirmed by Sanger sequencing. PubMed, Web of Science, CNKI and Wanfang Data were searched, and all publications that met the inclusion criteria were carefully screened. Any individual patient without a detailed description of clinical phenotype was excluded. Results: Our two patients manifested delayed motor milestones and muscle wasting of both lower extremities. The diagnosis was further confirmed as SMALED1. Genetic testing revealed heterozygous DYNC1H1 mutations c.1792C>T and c.790C>G respectively, the latter of which is a novel dominant mutation. Genotype-phenotype analysis of DYNC1H1 variants and neuromuscular diseases revealed that mutations in the DYN1 region of DYNC1H1 protein were associated with a more severe phenotype, more complicated symptoms and more CNS involvement than that in the DHC_N1 region. Conclusions: Our study potentially expanded the knowledge of the phenotypic and genetic spectrum of neuromuscular diseases caused by DYNC1H1 mutations. The genotype-phenotype correlation may reflect the pathogenesis underlying dyneinopathy caused by DYNC1H1 mutations.